Endovascular Intervention in a Narrowing Vessel of the Left Vertebral Artery with Bilateral Common Carotid Artery Occlusion and Aneurysm Rupture and Hemorrhage in the V4 Segment of the Right Vertebral Artery. (19th May 2022) - Feng, Yang; Peng, Han; Xiang, Xin; Zeng, Xi; Sun, Bin; Lin, Hongyi; Wang, Xiaofeng; Yang, Hua
Abstract : In this study, a case of bilateral common carotid artery occlusion and aneurysm in the V4 segment of the right vertebral artery with constriction of the left vertebral artery is presented. By improving digital subtraction angiography, an elderly female patient with subarachnoid haemorrhage (SAH) was diagnosed with a V4 segment of right vertebral artery aneurysm, a microaneurysm at the beginning of basilar aneurysms, bilateral common carotid artery occlusion, and narrowing vessel of left vertebral artery (DSA). Through the compensation of the basilar artery, the bilateral vertebral arteries provide intracranial and extracranial blood. Because the vertebral artery is narrowed, the right vertebral artery has priority in intracranial and extracranial blood delivery. Many members of the patient's immediate family have vasculitis, which has yet to be proven by appropriate laboratory testing but is thought to be the major cause of big artery occlusion. After cerebral angiography, the major source of this subarachnoid haemorrhage was determined to be a V4 segment of right vertebral artery aneurysm. Endovascular stent-assisted coil embolization was used to treat a V4 section of the right vertebral artery aneurysm. Because the basilar aneurysm was distal to the artery, interventional embolization was difficult to do, and it was not the major cause of the subarachnoid haemorrhage, the patient was advised to have follow-up surveillance, and she recovered well following the procedure. The combination of endovascular intervention of bilateral common carotid artery blockage and V4 segment of right vertebral artery aneurysm yielded excellent clinical outcomes in this instance. Endovascular treatment of a bilateral common carotid artery blockage paired with a V4 segment of a right vertebral artery aneurysm yielded excellent clinical outcomes in this patient, although long-term follow-up is necessary.